2000
DOI: 10.1073/pnas.97.15.8566
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of eIF2Bγ and eIF2γ as cofactors of hepatitis C virus internal ribosome entry site-mediated translation using a functional genomics approach

Abstract: CorrectionsMICROBIOLOGY. For the article ''Identification of eIF2B␥ and eIF2␥ as cofactors of hepatitis C virus internal ribosome entry site-mediated translation using a functional genomics approach''

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 23 publications
2
54
0
Order By: Relevance
“…Phenotypic screens using such libraries can reveal new potential therapeutic targets as well as new functions of known genes, as has been done using randomized ribozyme libraries instead of siRNAs (Kruger et al 2000;Li et al 2000;. Any siRNA sequences that may be lethal to the host cell will be eliminated from the library, and sequences toxic enough to retard growth can be eliminated by allowing the cells harboring nontoxic siRNAs to outgrow them.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic screens using such libraries can reveal new potential therapeutic targets as well as new functions of known genes, as has been done using randomized ribozyme libraries instead of siRNAs (Kruger et al 2000;Li et al 2000;. Any siRNA sequences that may be lethal to the host cell will be eliminated from the library, and sequences toxic enough to retard growth can be eliminated by allowing the cells harboring nontoxic siRNAs to outgrow them.…”
Section: Discussionmentioning
confidence: 99%
“…EIF2S3 binds to the 5Ј nontranslated region (5Ј NTR) of HCV and has been reported to modulate HCV translation (35). PTBP1 binds to both 5Ј and 3Ј NTRs, suggesting a possible interaction between the 5Ј and 3Ј termini of HCV RNA (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…These properties would be expected to render HCV translation relatively resistant to cellular stresses or apoptosis-inducing conditions that compromise the availability or integrity of eIF4E, eIF4B, and eIF4G (Bushell et al , 2001Clemens et al 2000). However HCV IRES-driven protein synthesis may potentially still be sensitive to regulation of eIF2 and/or eIF2B activity (Kruger et al 2000). Previous reports have suggested that the function of several cellular IRESes is resistant to inhibition in stressed or apoptotic cells (Coldwell et al 2000;Holcik et al 2000a;Stoneley et al 2000).…”
Section: Introductionmentioning
confidence: 99%